Explore our collection - National Portrait Gallery (2005)
[Dt.:] Die National Portrait Gallery präsentiert die Geschichte der britischen Porträtkunst von seinen Anfängen bis in die Gegenwart. Die Sammlung umfaßt über 330.000 Arbeiten (Gemälde, Skulpturen, Zeichnungen, Druckgraphik und Photographien). Die Bestände des Museums sind über die Online-Bilddatenbank zugänglich. Die Bilddatenbank kann über eine einfache und erweiterte Suche, sowie über verschiedene Browsingeinstiege durchsucht werden. Die Suchergebnisse umfassen kleinformatige Abbildungen (Thumbnails) mit knappen Katalogeinträgen. - [Engl.:] The National Portrait Gallery's collection demonstrates the history of British portraiture from its beginning, through the contortions of caricature and the crisis caused by the advent of photography, to the edge of abstraction. The National Portrait Gallery's collection is accessible in the online database. The collection can be searched by different ways: a simple search to find pictures of particular people, pictures by particular artists or particular pictures, by their titles; an advanced search and different browsing possibilities are available.